Proteomic analysis reveals presence of platelet microparticles in endothelial progenitor cell cultures - Prokopi, Marianna; Pula, Giordano; Mayr, Ursula; Devue, Cécile; Gallagher, Joy; Xiao, Qingzhong; Boulanger, Chantal M; Westwood, Nigel; Urbich, Carmen; Willeit, Johann; Steiner, Marianne; Breuss, Johannes; et al. (My University, 2009)
The concept of endothelial progenitor cells (EPCs) has attracted considerable interest in cardiovascular research, but despite a decade of research there are still no specific markers for EPCs and results from clinical trials remain controversial. Using liquid chromatography-tandem mass spectrometry, we analyzed the protein composition of microparticles (MPs) originating from the cell surface of EPC cultures. Our data revealed that the conventional methods for isolating mononuclear cells lead to a contamination with platelet proteins. Notably, platelets readily disintegrate into platelet MPs. These platelet MPs are taken up by the mononuclear cell population, which acquires "endothelial" characteristics (CD31, von Willebrand factor [VWF], lectin-binding), and angiogenic properties. In a large population-based study (n = 526), platelets emerged as a positive predictor for the number of colony-forming units and early outgrowth EPCs. Our study provides the first evidence that the cell type consistent with current definitions of an EPC phenotype may arise from an uptake of platelet MPs by mononuclear cells resulting in a gross misinterpretation of their cellular progeny. These findings demonstrate the advantage of using an unbiased proteomic approach to assess cellular phenotypes and advise caution in attributing the benefits in clinical trials using unselected bone marrow mononuclear cells (BMCs) to stem cell-mediated repair.
Keywords: Circulating EPCs; Stem Cells; Endothelial Cells